Development of Selangor dengue information system using desktop, web-based and mobile GIS for managing dengue disease in Selangor / Muhammad Jamaluddin Bazlan - Bazlan, Muhammad Jamaluddin (2017)
Dengue is one of the major heath problems in Malaysia especially in Selangor, where the local current situation of the disease have been concerning public communities in the state. There are some dengue information system existed in the country, but the State Health Department of Selangor (JKNS) has requested in developing any proposed system in the department, where it needs to consider the aspects of spatial information sharing function, cost efficiency, and the staff capability in spatial data handling. Therefore, Geographical Dengue Information System (GeoDIS), is known as Selangor Dengue Information System (SDIS) was developed using three different GIS platforms (i.e Desktop GIS, Web-based GIS and mobile GIS) for practical implementation in the JKNS. Licensed and free open source software, consisting of Visual Basic, Microsoft .Office Access, and Quantum GIS (QGIS) were employed to produce dengue map and geodatabase system. Meanwhile, Map Guide and OOO webhost were integrated to create online web base dengue map and publishing, then the mobile dengue applications was utilized with Wikitude for augmented reality visualization. Standard Development Lifecycle (SDLC) is formal guidelines for system development, were adopted to achieve the objectives of the study; i) to study the user requirements for developing the prototype of SDIS, ii) to design and develop the SDIS, and iii) to implement and test the performance of the SDIS applications among the selected respondents in the department. Result from user requirement showed the average performance of current dengue system in the department need to enhance by applying a low cost and user friendly GIS-based information system. More than 87 percents of the respondents were agreed that the proposed system should contain basic GIS components/funtions for the disease applications, such as data management, mapping and visualisation, data processing, data analysis and information sharing. The study also constructed an architectural framework for the SDIS with the aprroach of conceptual, logical and physical design, which is an useful guideline for relating model entities in the system. This framework was insighfully customed to develop the SDIS application, consisting of three menu phases; patient registration system, web-based system, and mobile application system. Furthermore, the SDIS offered five significant functions or components as requested by respondents, including patient data management, disease mapping and pattern visualization, geoprocessing and multicriteria analysis, and spatial information sharing. Overall, the SDIS was designed to integrate epidemiological information with the corresponding geographical components for local dengue spatial decision making and management tool in the JKNS. The prototype of SDIS was tested and 86% of respondents were satisfied with the system modules and components, however the component such as data management and storage capacity need to be heightened for big data manipulation, protection and standardization.